Human Abuse Potential of Oral NKTR-181 in Recreational Opioid Users: A Randomized, Double-Blind, Crossover Study. Issue 2 (25th September 2019) - Ge, Xue; Henningfield, Jack E; Siddhanti, Suresh; Jobes, Janet; Lu, Lin; Xie, Sunny; Ziola, Margaret; Kelsh, Debra; Vince, Bradley; Di Fonzo, Carlo J; Tagliaferri, Mary; Zalevsky, Jonathan; et al.
Abstract: Objective: To evaluate the human abuse potential, pharmacokinetics, pharmacodynamics, and safety of oral NKTR-181 (oxycodegol), a novel full mu-opioid receptor agonist, relative to oral oxycodone. Design: This double-blind, randomized, single-dose, crossover human abuse potential study was conducted in healthy, adult, non–physically dependent recreational opioid users. Setting: Inpatient clinical research site. Subjects: Seventy-one subjects randomized (95.7% male, 65.2% African American, mean age = 31.7 years). Methods: The primary objective was to compare two therapeutic doses of NKTR-181 (400 and 600 mg) with 40 and 60 mg of oxycodone and a supratherapeutic dose (1200 mg) of NKTR-181 with 60 mg of oxycodone using visual analog scale (VAS) ratings for Drug Liking "at this moment" (Drug Liking). Secondary objectives included VAS ratings for other subjective measures, and central nervous system (CNS) mu-opioid effects were assessed using pupillometry. Each subject received single oral doses of five treatments and matching placebo. Results: Compared with 40 and 60 mg of oxycodone, the maximum mean Drug Liking score at 400 and 600 mg NKTR-181 was significantly lower, and the rate of onset and extent of Drug Liking for all NKTR-181 doses in the first two hours postdose were also significantly lower. Delayed attenuated Drug Liking and pupillary miosis response following administration of NKTR-181 vs oxycodone were consistent with slower NKTR-181 CNS entry kinetics and mu-opioid receptor binding. No adverse events were rated as severe, and somnolence and dizziness occurred more frequently when subjects received oxycodone. Conclusions: NKTR-181 at oral doses of 400 and 600 mg showed significantly fewer and less severe subjective effects accepted as representative of opioid abuse potential, such as lower peak Drug Liking in recreational opioid users, than 40 and 60 mg of oxycodone.